D6.3 Future Greenhouse Design Study Report - Vrakking, Vincent; Maiwald, Volker; Schubert, Daniel; Zabel, Paul; Waclavicek, Rene; Rossetti, Vittorio; Rousek, Thomas; Adami, Marco; Gorga, I. (Zenodo, 2019)
This document details the preliminary design of a future planetary greenhouse, adapted from the Mobile Test Facility which was built and operated as part of the EDEN ISS project. Lessons learned from the Antarctic operations phase, as well as the mission scenario for a planetary greenhouse, were considered to establish the system requirements. Based on these requirements, a preliminary design of the greenhouse structure and subsystems was developed. The preliminary design presented in this document is a deployable cylindrical structure, with rigid end caps and an inflatable membrane shell in between. The structure has been sized to fit within the payload fairing of a Falcon 9 launcher, with a stowed configuration diameter of 4 meters and a length of 6.3 meters. Following deployment, the structure is envisioned to be 12.9 meters long and the membrane shell will expand to a diameter of 5 meters. An estimation of the subsystem volumes was made, in order to design the internal configuration. This internal layout offers 30.8 m² of cultivation area, a more than twofold increase over the existing Mobile Test Facility. Mass estimations were made for the different elements to determine whether or not a single launch scenario with a Falcon 9 launcher is feasible or not. The total estimated mass, with a 20% margin to account for uncertainties, was found to be lower than the launch mass capacity of the launcher.